2015
DOI: 10.9738/intsurg-d-14-00217.1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sigmoidectomy for a Patient With Situs Inversus Totalis: Effect of Changing Operator Position

Abstract: Situs inversus totalis (SIT) is a rare congenital condition in which the abdominal and thoracic organs are on the opposite sides to their normal anatomic positions. Reports of laparoscopic surgery for colorectal cancer with SIT are very few. Due to the mirror-image transposition of organs and vascular abnormalities, laparoscopic surgery for patients with SIT is technically complicated. Therefore, it has been reported as easier for left-handed surgeons. This report presents that operative procedures can be cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Due to the different anatomical positions of the organs, surgical procedures in patients with SIT are considered more difficult than those in others, particularly laparoscopic surgery. While, laparoscopic colorectal surgery (LCS) is currently the standard procedure for colorectal cancers (CRC), including the present case, only eight cases of LCS for colorectal cancer in patients with SIT have been reported [3] , [4] , [5] , [6] , [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 79%
“…Due to the different anatomical positions of the organs, surgical procedures in patients with SIT are considered more difficult than those in others, particularly laparoscopic surgery. While, laparoscopic colorectal surgery (LCS) is currently the standard procedure for colorectal cancers (CRC), including the present case, only eight cases of LCS for colorectal cancer in patients with SIT have been reported [3] , [4] , [5] , [6] , [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 79%
“…9 We found only 8 cases of laparoscopic surgery for colorectal malignancy complicated by SIT reported in the English literature, and only one of them involved treatment with single-site laparoscopic surgery. [1][2][3][4][5][6][7][8] Laparoscopic surgery is considered to be more difficult in patients with SIT than in other patients because of the mirror-image anatomy. It is therefore important for the safe and effective performance of laparoscopic surgery in patients with SIT to first undertake a preoperative examination, because the frequency of abnormal vascularization of arteries and veins is high, in addition to the problems posed by the mirror-image presentation of the viscera.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of this surgery for colorectal cancer is rapidly becoming widespread, we found only 8 case reports in patients with SIT. [1][2][3][4][5][6][7][8] To our knowledge, thus far, there is only 1 case report of single-site laparoscopic surgery in SIT. 8 We present another case.…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons in these past cases in Japan performed surgery while standing opposite to their normal positions, whereas surgeons in the Korean cases stood in a normal position. Yaegashi et al reported that changing surgeons’ standing positions during surgery in patients with SIT is effective in laparoscopic surgery . We selected the opposite port locations and standing positions and used a second monitor to recognize the normal images during surgery.…”
Section: Discussionmentioning
confidence: 99%